Impact of Exam Stress on Oral Hygiene and Periodontal Indices of Yazd Dental Students in 2024 - Fahimeh Rashidi Maybodi; Mehrdad Homaei Mehr; Maryam Sabet (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Exams can be a potential cause of increasing students' academic stress. The current study examined the impact of exam-related stress on the oral health practices and periodontal measures of Yazd dental students in 2024. Methods: In this cross-sectional study, a census was conducted on 42 fourth-year students. Following the acquisition of consent, two weeks prior and during the final week of the exams, measurements of the plaque index (PI), gingival index (GI), and stress levels were taken using the Gadzella questionnaire for comparison. Furthermore, the connection among gender, living apart from the family, and dormitory life concerning stress levels was explored. The students’ oral health habits of the students were also assessed via self-reporting. No guidance or hygiene instructions were given to the participants, and if there was any alternation in the frequency of brushing or flossing, the sample was excluded. Data analysis was conducted using SPSS22 software along with and paired T, Wilcoxon and Pearson tests. Results: Gender, living with the family or independently, and living in a dormitory or a private home had no impact on students’ stress levels. The alternations in the PI and GI indices as well as academic stress changes were notable (P-value< 0.001). No significant correlation was detected between PI and GI concerning the frequently of brushing or flossing (P-value >0.05). Conclusion: Taking into account the rise among students during exam periods along with the absents of a link between these changes and their overall oral hygiene habits, it seems that the stress from exams adversely affects oral health.